Does The BBN KB Incentive Policy Increase Ownership Of Battery-Based Electric Vehicles? Indonesia Case Study - Ramadhan, Risza Galas; Khoirunurrofik, Khoirunurrofik (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
Indonesia's commitment by 2060 is to reduce greenhouse gas emissions and realize net zero emissions. The transition of electric vehicles in the transportation sector with renewable energy is a solution to reduce emissions. However, the ownership rate of battery-based electric vehicles in Indonesia is still low. This study empirically discusses the effect of the BBN KB incentive policy designed to encourage ownership of battery-based electric vehicles in Indonesia. To determine the effect of the BBN KB incentive policy on battery-based electric vehicle ownership, a Moderated Regression Analysis (MRA) panel data analysis with Pooled Ordinary Least Square (POLS) estimation technique is used using secondary data from 34 provinces in Indonesia from 2019-2022. The results of the analysis found that the BBN KB incentive policy has a significant effect on increasing ownership of electric vehicles, especially battery-based electric cars in Indonesia. The factors of the number of charging infrastructure (SPKLU), consumer awareness, fuel prices and open unemployment rates have a significant influence on ownership of battery-based electric motorized vehicles. Analysis on the island of Java explains that there is a significant effect on increasing ownership of battery-based electric car vehicles after the policy is implemented, while on non-Java island the BBN KB incentive policy shows an insignificant impact on increasing ownership of battery-based electric vehicles, especially 4-wheelers.